Odpowiedzi

2010-03-05T19:35:07+01:00
A) ( 3x - 2 )( 4x + 5 ) =12x²-15x-8x-10=12x²-23x-10
b) ( -2x + 4 )( 6x - 8 ) = -12x²+16x+24x-32=-12x²+40x-32
c) ( -6x - 9 )( 2x + 3 )= -12x²-18x-18x-27=-12x²-36x-27
d) ( x - 7 )( -x - 5 ) =-x²-5x+7x+35=-x²+2x+35
12 3 12
2010-03-06T01:31:10+01:00
A ) ( 3x - 2 )( 4x + 5 ) =12x)2( - 15x - 8x - 10 = 12x)2( - 23x - 10
b) ( -2x + 4 )( 6x - 8 ) = -12x)2( + 16x + 24x - 32 = -12x)2( + 40x -32
c) ( -6x - 9 )( 2x + 3 )= -12x)2( - 18x - 18x - 27 = -12x)2( - 36x - 27
d) ( x - 7 )( -x - 5 ) = -x)2( - 5x + 7x + 35 = -x)2( + 2x + 35


)2( - do potęgi drugiej ;)
4 2 4